Medication state at the time of the offense: Medication noncompliance, insight and criminal responsibility. (20th April 2018) - Parrott, Caroline Titcomb; Jones, Michelle A.; Brodsky, Stanley L.; Shealy, Clayton
Abstract: This study used a mixed quantitative‐qualitative methodology to examine whether mock jurors considered a defendant's meta‐responsibility – specifically, the defendant's medication noncompliance and degree of insight into his/her schizophrenia – when determining the person's criminal responsibility. The degree of expert witness explanation regarding these factors was also varied. Participants ( n = 173) were grouped into 30 juries, randomized across five conditions, and shown mock testimony and attorney arguments based on a real not guilty by reason of insanity court case. Linear mixed‐modeling analysis showed that manipulations of medication compliance, insight, and expert testimony elaboration did not predict differential verdict and meta‐responsibility outcomes. Nevertheless, qualitative exploration of focus groups from five juries ( n = 29) indicated that participants across groups strongly considered meta‐responsibility, but did so in a way that, along with a host of other considerations, suggested mock jurors were unable and/or unwilling to follow their duties as the triers of fact. Implications for legal participants, expert witnesses, and researchers are discussed.